2009
DOI: 10.1099/mic.0.027862-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis of global gene regulation by A-factor in Streptomyces griseus

Abstract: A-factor (2-isocapryloyl-3R-hydroxymethyl-γ-butyrolactone) is a microbial hormone that triggers morphological differentiation and secondary metabolism in Streptomyces griseus. The effects of A-factor on global gene expression were determined by DNA microarray analysis of transcriptomes obtained with the A-factor-deficient mutant ΔafsA. A-factor was added at a concentration of 25 ng ml−1 to mutant ΔafsA at the middle of the exponential growth phase, and RNA samples were prepared from the cells grown after A-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…In fact, its complex regulation system has been mostly established. 41 However, not so many biosynthetic enzymes have been characterized even now because, probably, the biosynthetic pathway for streptomycin is too unique to predict appropriate functions compared with other aminoglycoside biosynthetic genes. Among the streptomycin biosynthetic enzymes, Gln:scyllo-inosose aminotransferase StsC 15 and Arg:inosamine-phosphate amidinotransferase StrB1 16 are characterized biochemically.…”
Section: Other Aminoglycoside Biosynthetic Genesmentioning
confidence: 99%
“…In fact, its complex regulation system has been mostly established. 41 However, not so many biosynthetic enzymes have been characterized even now because, probably, the biosynthetic pathway for streptomycin is too unique to predict appropriate functions compared with other aminoglycoside biosynthetic genes. Among the streptomycin biosynthetic enzymes, Gln:scyllo-inosose aminotransferase StsC 15 and Arg:inosamine-phosphate amidinotransferase StrB1 16 are characterized biochemically.…”
Section: Other Aminoglycoside Biosynthetic Genesmentioning
confidence: 99%
“…Because gcoA was indicated to be a direct target of AdpA (19), a master regulator of secondary metabolism and morphological differentiation in S. griseus, we also analyzed by GC-MS the extracts of crude cell lysate of an adpA-deleted (⌬adpA) mutant (Fig. 3, iii).…”
Section: Production Of (ϩ)-Caryolan-1-ol By Wild-type S Griseus But mentioning
confidence: 99%
“…The other two genes encode single-domain SC homologs (SGR2079 and SGR6065). Interestingly, our transcriptome analysis showed that the SGR2079 gene is transcribed in wild-type S. griseus in an AdpA-dependent manner (19), indicating that SGR2079 is involved in the production of one of the secondary metabolites under the control of A-factor. SGR2079 (335 amino acids) shows 29% amino acid sequence identity with the pentalenene synthase from Streptomyces sp.…”
mentioning
confidence: 99%
“…In S. griseus, adpA is the sole target of the A-factor receptor (ArpA). By applying microarray and electrophoretic mobility shift assay (EMSA) analysis, AdpA has been shown to directly bind 37 promoter regions to activate 72 genes throughout the chromosome, including strR, the pathway-specific activator for streptomycin biosynthesis (Hara et al, 2009). While in S. coelicolor, adpA c transcription does not depend on the butyrolactone system, the DadpA c mutant is conditionally defective in morphological differentiation.…”
Section: Introductionmentioning
confidence: 99%